Кочерган Μ. П. Основи зіставного мовознавства - Мацько, Л.; Корольова, А. (Мовознавство, 2007)
Рецензія на книгу: Кочерган Μ. П. Основи зіставного мовознавства: Підручник
К. : Вид. центр «Академія», 2006.— 424 с.